Technical Challenges of Multipollutant Air Quality Management - Hidy, George M.; Brook, Jeffrey R.; Demerjian, Kenneth L.; Molina, Luisa T.; Pennell, William T.; Scheffe, Richard D. (Springer Netherlands : Imprint: Springer, 2011)
Recent critiques of air quality management approaches currently employed in developed and many developing countries have suggested that efficiencies could be achieved if air quality management practices shifted from pollutant-by-pollutant approaches to a comprehensive multipollutant approach in which emission reduction decisions are based on relative risk and evaluated on their effectiveness in meeting environmental and health goals. This book assesses our technical readiness to undertake such an approach, and it outlines the technical developments that will be needed to achieve a risk-based approach air quality management that includes means for measuring the effectiveness of management decisions.